2000
DOI: 10.1159/000027478
|View full text |Cite
|
Sign up to set email alerts
|

Primary Open-Angle Glaucoma Is Associated with Sleep Apnea Syndrome

Abstract: Introduction: The etiology of primary open-angle glaucoma remains unclear. Various risk factors, including vascular abnormalities, have been associated with this disease. Sleep-associated diseases, like sleep apnea syndrome, might also represent a risk factor. Sleep apnea syndrome is characterized by repetitive upper airway obstructions during sleep, inducing hypoxia and sleep disruption with the risk of cardiovascular and neurological sequelae. In this study, we determined the prevalence of sleep apnea syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 9 publications
3
73
0
7
Order By: Relevance
“…Ocular associations reported with OSAHS include floppy eyelid syndrome (FES), blepharoptosis, lower lid ectropion, blepharochalasis, eyelash ptosis, lacrimal gland prolapse, papillary conjunctivitis, filamentary or infectious keratitis, recurrent corneal erosion, keratoconus, optic neuropathy, papilloedema, and glaucoma. [3][4][5][6][7][8][9][10][11][12][13] Specific disease management uses the basic concept of gentle pressurisation of the upper airway during sleep to prevent the collapse of the pharynx. Continuous positive airway pressure (CPAP) administered through a nasal or face mask has remained the mainstay of treatment in OSAHS since its advent in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular associations reported with OSAHS include floppy eyelid syndrome (FES), blepharoptosis, lower lid ectropion, blepharochalasis, eyelash ptosis, lacrimal gland prolapse, papillary conjunctivitis, filamentary or infectious keratitis, recurrent corneal erosion, keratoconus, optic neuropathy, papilloedema, and glaucoma. [3][4][5][6][7][8][9][10][11][12][13] Specific disease management uses the basic concept of gentle pressurisation of the upper airway during sleep to prevent the collapse of the pharynx. Continuous positive airway pressure (CPAP) administered through a nasal or face mask has remained the mainstay of treatment in OSAHS since its advent in the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…1 OSAS has been reported in association with primary open angle glaucoma. 1 Geyer et al 2 found equal prevalence of glaucoma in OSAS as in the general population. Ophthalmic findings in OSAS are floppy eyelid syndrome, 3,4 keratoconus, 5 papilloedema, 6 and ischaemic optic neuropathy.…”
Section: Commentmentioning
confidence: 95%
“…Complications associated with alloplastic implants (silicone/silastic/supramid) are rare. 1 However, they can occur some considerable time after surgery. 2 A 36-year-old Caucasian male presented with complete lower eyelid retraction 3 years after silicone sheet orbital floor implant.…”
Section: Commentmentioning
confidence: 99%
“…Majon DS et al, [5] diagnosed sleep apnoea in 20% POAG patients by using transcutaneous finger oxymetry by calculating the oxygen disturbance index. In our study, the diagnosis of sleep apnoea was based on a combination of the positive questionnaire responses and the positive polysomnography results.…”
Section: The Association Of Sleep Apnoea In the Poag Casesmentioning
confidence: 99%